2009
DOI: 10.1111/j.1740-8709.2009.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting influences on UK mothers' decisions to introduce solid foods to their infants

Abstract: Adherence to recommendations to wait until 6 months to introduce solid foods into infants' diets is very poor. An in-depth understanding of the factors involved in this decision is essential if health practitioners are to offer suitable advice and health education. A cross-sectional electronic questionnaire study was conducted with 105 mothers recruited via UK-based Internet parenting discussion forums. Ratings of variables important in making the decision to introduce solid foods were analyzed using factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
162
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(168 citation statements)
references
References 30 publications
5
162
1
Order By: Relevance
“…Confusion felt towards official weaning guidelines was mentioned in this study, in agreement with O'Key and Hugh-Jones [31]. This confusion has previously been perceived as difficult and stressful [26]. As this was a qualitative study, we did not seek to quantify knowledge of infant feeding guidelines.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Confusion felt towards official weaning guidelines was mentioned in this study, in agreement with O'Key and Hugh-Jones [31]. This confusion has previously been perceived as difficult and stressful [26]. As this was a qualitative study, we did not seek to quantify knowledge of infant feeding guidelines.…”
Section: Discussionsupporting
confidence: 61%
“…The facilitators of the focus groups were not health professionals, thus reducing a social desirability bias and were independent of baby food manufacturers. In considering possible bias introduced by the sample and recruitment strategy, it must be highlighted that many other published studies investigating mothers' opinions on complementary feeding have used either a self-selected or convenience sample, often recruited via online mother and baby discussion forums and often also limited to those who are using a specific weaning style [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…McKenzie (2003), described similar failures to connection which she categorized as barriers due to their effect on future seeking behaviours. Similar conflicts are reported by Arden (2009) with mothers having to weigh up official recommendations about when to wean infants with more tailored advice from health professionals, and advice from friends and family. Our study participants reported drawing on maternal instinct to resolve such conflict, one mother stating: I just like, follow my instinct.…”
mentioning
confidence: 83%
“…[Agreement from group] I mean that happens all the time. Arden (2009) ommonly reported reasons for decisions about when to introduce solids to an infant. She describes the education recommendations, more tailored guidance from health professionals, what mothers recognise in the I O K H -Jones (2010) report that claims about instinct or intuition are most common when decisions are in opposition to recommendations from health professionals.…”
mentioning
confidence: 99%
“…Previous studies have indicated that the parental decision to begin weaning earlier than recommended is associated with a range of signals, such as the infant waking at night, seeming hungry or unsatisfied by milk, or reaching for food (9)(10)(11) . However, despite clarification from the DH (12) , there is little consensus among mothers about the cues they deem significant (10) . Given that readiness for solids is a developmental process, there has been the suggestion that health visitors may also find it difficult to remain consistent with published guidelines while offering advice tailored to signals from the infant (9,10) and as a result commonly suggest weaning earlier than the guidelines (13) .…”
mentioning
confidence: 99%